Expressing banana transcription factor MaERFVII3 in Arabidopsis confers enhanced waterlogging tolerance and root growth - Teoh, Ee Yang; Teo, Chee How; Baharum, Nadiya Akmal; Tan, Boon Chin (PeerJ, 2024)
Background: Waterlogging poses a significant threat to plant growth and yield worldwide. Identifying the genes responsible for mitigating waterlogging stress is crucial. Ethylene-responsive factors (ERFs) are transcriptional regulators that respond to various biotic and abiotic stresses in plants. However, their roles and involvement in responding to waterlogging stress remain largely unexplored. Hence, this study aimed to elucidate the role of ERFs in enhancing banana plant resilience to waterlogging. Methods: We hypothesized that introducing a group VII ERF transcription factor in Arabidopsis could enhance waterlogging stress tolerance. To test this hypothesis, we isolated MaERFVII3 from banana roots, where it exhibited a significant induction in response to waterlogging stress. The isolated MaERFVII3 was introduced into Arabidopsis plants for functional gene studies. Results: Compared with wild-type plants, the MaERFVII3-expressing Arabidopsis showed increased survival and biomass under waterlogging stress. Furthermore, the abundance of transcripts related to waterlogging and hypoxia response showed an elevation in transgenic plants but a decrease in wild-type and empty vector plants when exposed to waterlogging stress. Our results demonstrate the significant contribution of MaERFVII3 to waterlogging tolerance in Arabidopsis, providing baseline data for further exploration and potentially contributing to crop improvement programs.